Development of Android-Based Banten Cultural Introduction Media for Children at the Amanah As-Sodiqiah Rajeg Orphanage - Saputri, Fiqih Hana; Br Bangun, Eka Uliyanti Putri; Usni, Al Asmaul (JURNAL SISFOTEK GLOBAL, 2024)
This research started with the demand for innovation in the world of learning, along with the increasingly rapid development of technology that is beneficial to the world of education, one of which is the use of Android-based educational games to introduce Banten culture. This research aims to make it easier for orphanage children to learn about Banten culture in Indonesia. Another reason for the purpose of making this educational game is none other than to get an idea of the differences in the results of foster children's knowledge between educational games and books of knowledge. The software that I use is Construct 2. The research uses data collection methods and a problem approach which includes literature, observation, design and testing and implementation. The result shows that the application has been created has a percentage of 79.42% where this value means that this application is fairly good.